The Influence of Service Quality on Tourist Loyalty at Pulau Merah Beach Tourist Destination, Banyuwangi, Indonesia - Endang Suprihatin; Endah Susanti (SINGOSARI, 2026)
The purpose of this study is to examine visitor satisfaction in the marine tourism service industry, particularly at Pulau Merah Beach, Banyuwangi, Indonesia. As one of the flagship programs of the local government, Pulau Merah Beach promotes ecotourism as a strategic sector that receives special attention and continuous development to enhance local economic growth. In addition, the destination aims to attract tourists by offering the unique experience of enjoying its pristine natural coastal environment, which represents a distinctive local advantage not found in many other regions of Indonesia. The validity test results indicated that all questionnaire items had item-total correlation coefficients greater than 0.30 and were statistically significant at the 0.05 level, confirming that the instrument was valid for measuring the constructs of service quality and tourist loyalty. Reliability testing using Cronbach's Alpha produced coefficients of 0.876 for the service quality variable and 0.842 for the tourist loyalty variable. These values demonstrate excellent internal consistency, indicating that the research instrument is highly reliable and that the collected data are suitable for further analysis. Instrument validation is essential to ensure that the findings accurately reflect the actual conditions in the field rather than measurement errors. Furthermore, Pearson correlation analysis was conducted to examine the relationship between service quality and tourist loyalty. The results revealed a correlation coefficient of r = 0.621 with a significance level of p = 0.000, indicating a strong, positive, and statistically significant relationship between the two variables. These findings suggest that higher perceived service quality is associated with greater tourist loyalty toward the destination.